2016
DOI: 10.1007/s11136-016-1378-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of body image impairment on the quality of life of non-operated Portuguese female IBD patients

Abstract: These findings suggest that non-operated female patients are subject to pervasive and harmful effects of body image impairment on psychological and physical functioning. Therefore, psychological interventions aiming to target body dissatisfaction should be implemented in the health care of IBD, independently of patients' operative status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 32 publications
6
30
0
Order By: Relevance
“…Database searches identified 587 records and 5712 14 22–76 studies were included, with some studies eligible for multiple questions (see figure 1 for selection process and reasons for exclusion). All 57 papers reported using BI tools, 3114 22–26 30 31 33–39 42 47 50 51 53 54 58 60–65 67 69 71 72 reported prevalence or mean/median BI scores, 1614 23 24 30 34–36 47 54 58 60 61 63 65 67 71 studies presented factors associated with BID and 814 22–24 34 61 65 71 studies reported correlations between QoL and BI.…”
Section: Resultsmentioning
confidence: 99%
“…Database searches identified 587 records and 5712 14 22–76 studies were included, with some studies eligible for multiple questions (see figure 1 for selection process and reasons for exclusion). All 57 papers reported using BI tools, 3114 22–26 30 31 33–39 42 47 50 51 53 54 58 60–65 67 69 71 72 reported prevalence or mean/median BI scores, 1614 23 24 30 34–36 47 54 58 60 61 63 65 67 71 studies presented factors associated with BID and 814 22–24 34 61 65 71 studies reported correlations between QoL and BI.…”
Section: Resultsmentioning
confidence: 99%
“…Both frequency and intensity of fatigue are more prominent in the female population. IBD further has a negative impact on body image, more so in females than in males [63,64]. Reduced sexual activity is more frequently reported in female than male IBD patients (66.3 vs. 40.5%, p < 0.001) [64].…”
Section: Psychological Factorsmentioning
confidence: 99%
“…IBD often leads to feelings of shame, embarrassment and isolation, concerns regarding the risk of relapsing or developing cancer, difficulty in maintaining daily routines due to severe symptomatology that may arise abruptly, and struggles with body dissatisfaction and sexuality [4][5][6][7][8]. It has been reported that, even during periods of remission, IBD patients' QoL is significantly poorer in comparison with healthy controls, and that comorbid psychopathology is frequent [1,9,10].…”
Section: Inflammatory Bowel Disease and Psychological Distressmentioning
confidence: 99%
“…Cognitive fusion thus refers to "the relationship a person has with this or her own cognitive events, on a continuum from fused (dominated by, entangled, believed, taken literally) to defused (experienced as mental events and not necessarily to be acted upon)" [28]. IBD patients, when "fused" with their cognitions, may get entangled with illness-related thoughts (e.g., "these symptoms are never going away"; "my illness is too embarrassing for me to talk 7 about it with others"; "nobody will understand how this illness affects my life") [29] and consequently choose to behave as if they were literally true [30].…”
Section: Emotion Regulationmentioning
confidence: 99%